2003
DOI: 10.1021/jp035547p
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Reactive Halogens:  The Thermochemistry of Hg + {Cl2, Br2, BrCl, ClO, and BrO}

Abstract: Accurate reaction enthalpies have been calculated using the CCSD(T) method and sequences of correlation consistent basis sets for the reactions of Hg with a series of small halogen-containing molecules (Cl 2 , Br 2 , BrCl, ClO, and BrO). Explicit extrapolations to the complete basis set limit are used together with accurate treatments of core-valence correlation, scalar relativity, and spin-orbit effects in order to predict both reaction enthalpies of the title reactions and heats of formation of the intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
74
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 65 publications
8
74
2
Order By: Relevance
“…Field studies (Peleg et al, 2007;Lindberg et al, 2002), laboratory studies (Donohoue et al, 2006), quantum calculations (Goodsite et al, 2004;Cremer et al, 2008;Balabanov et al, 2003;Tossell, 2003), and modeling studies (Holmes et al, 2006(Holmes et al, , 2009Selin et al, 2007) consistently suggest 2 Authors wish to note that the use of geometric AMFs for this calculation is a simplification of the radiative transfer process. We have carried out full radiative transfer calculations that varied in the assumptions about the BrO vertical distribution and find this simplification equally represents the uncertainty arising from the lack of knowledge about the true BrO vertical distribution aloft.…”
Section: Measurement Resultsmentioning
confidence: 93%
“…Field studies (Peleg et al, 2007;Lindberg et al, 2002), laboratory studies (Donohoue et al, 2006), quantum calculations (Goodsite et al, 2004;Cremer et al, 2008;Balabanov et al, 2003;Tossell, 2003), and modeling studies (Holmes et al, 2006(Holmes et al, , 2009Selin et al, 2007) consistently suggest 2 Authors wish to note that the use of geometric AMFs for this calculation is a simplification of the radiative transfer process. We have carried out full radiative transfer calculations that varied in the assumptions about the BrO vertical distribution and find this simplification equally represents the uncertainty arising from the lack of knowledge about the true BrO vertical distribution aloft.…”
Section: Measurement Resultsmentioning
confidence: 93%
“…The Cl atom can also oxidize Hg 0 to produce HgCl (Balabanov and Peterson, 2003;Donohoue et al, 2005). found that a broad range of radical oxidants could oxidize HgBr and HgCl including Y ≡ NO 2 and HO 2 , the most abundant atmospheric radicals, as well as Y ≡ BrO, ClO, and Cl.…”
Section: Chemical Mechanismmentioning
confidence: 99%
“…There have been several quantum chemical studies of mercury compounds, [18,19, where those of the Peterson group [18,[21][22][23][24][25][26][27][28] and those by Tossell [29][30][31][32][33] are most noteworthy. Each of these investigations focused on selected mercury compounds HgX; however none of them attempted a comprehensive study of mercury bonding by varying X systematically within the periodic table.…”
Section: Bdea C H T U N G T R E N N U N G (Hgx)àbdea C H T U N G T R mentioning
confidence: 99%
“…However this reaction sequence can be excluded on the basis of theoretical calculations carried out herein and in the studies of others. [18][19][20][21][22][23][24][25][26][27][28][29][30] The reaction of elemental Hg with OH radicals is more likely considering a reaction energy of 12 kcal mol…”
mentioning
confidence: 99%